Transverse Competences Of Teamwork In A Virtual Environment - Cortés Méndez, Jairo Augusto (Ingeniería Solidaria, 2010)
This article presents a case study on the transverse competences of the course at Universitat Oberta of Catalunya (UOC) in the fi rst semester of the MyC course 2006-2007. This course is a part of the computer science’s curriculum in this university. The analysis explains how the transverse competences of teamwork have developed in a virtual environment; in the same way, the theories of competences proposed by the Tuning project and the investigations and documents of the TACEV research team about the teamwork in virtual environments are deal with.